Marshall Islands : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This report describes economic developments in the Marshall Islands during the 1990s. Real GDP grew by 3.7 percent in 1995. Copra production increased, owing mainly to more frequent inter-island transport services by government-owned ships. Construction activity was boosted by the availability of external concessional aid financing for a high school and a garment factory, foreign direct investment on a dry dock, and a government-sponsored 150-room hotel. Value added from the transport, communications, and energy sectors rose, owing in part to an improvement in the financial performance of government-owned enterprises.